New records of marine water mites (Acari: Hydrachnidia, Pontarachnidae) from the southern Black Sea (Sinop Bay, Turkey) - PESIC, V.; SEZGIN, M.; KARACUHA, M. E.; URKMEZ, D. (Mediterranean Marine Science, 2013)
New records of marine mites of the family Pontarachnidae Koenike, 1910 (Acari: Hydrachnidia) from the southern Black Sea (Sinop bay, Turkey) are presented. Two species, i.e., Pontarachna valkanovi Petrova, 1978 and Pontarachna adriatica Morselli, 1980 are recorded for the first time from Turkey. These are the first records of these species after its orginal description. Our study shows ecological differences between these species: Pontarachna valkanovi were collected from 3 m depth, while P. adraitica seems to be characteristic for deeper waters (10 m depth).